Characterizing molecular and behavioral changes arising from ROMK potassium channel deficiency in the cerebellum - Agrimi, Jacopo; Dunphy, Aidan J.; Zhong, Justin C.; Zhang, Wenxi; Sbaiti, Naeem; Turner, Daniel R.; Bernardele, Lucia; Foster, D. Brian; O’Rourke, Brian; Paolocci, Nazareno; Papanicolaou, Kyriakos N. (Frontiers in Behavioral Neuroscience, 2026)
The cerebellum is critically involved in both motor coordination and affective regulation, and growing evidence suggests that cerebellar dysfunction contributes to neuropsychiatric disorders. While much attention has focused on synaptic signaling and calcium homeostasis, the role of potassium channels in cerebellar function remains relatively understudied. Here, we investigated the role of the potassium channel ROMK (renal outer medulla K+ channel) in cerebellar signaling and behavior using cre/loxP gene knockout in Pcp2cre-expressing cells. Surprisingly, ROMK expression was detected in a distinct cell population within the cerebellar granule layer, rather than in Purkinje cells, yet this expression was effectively targeted by Pcp2cre-mediated recombination. Mutant mice showed normal Purkinje cell density and soma size, but increased dendrite diameter. At the molecular level, we observed downregulation of cerebellar subtype-specific genes and potassium channel subunits, along with changes in markers of translational signaling. Increased presence of GFAP-positive cells further suggested underlying neuronal stress in the ROMK-deficient cerebellum. Behaviorally, ROMK-deficient mice exhibited clear impairments in motor coordination and heightened anxiety-like behavior in the elevated plus maze (EPM). Our findings link ROMK loss to molecular and cellular remodeling in the cerebellum and support the idea that ROMK contributes to neural circuits that regulate complex behaviors, providing a framework for further studies in this direction.